2008
DOI: 10.1016/j.ijsu.2008.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Microwave tumors ablation: Principles, clinical applications and review of preliminary experiences

Abstract: Local ablative techniques have been developed to enable local control of unresectable tumors. Ablation has been performed with several modalities including ethanol ablation, laser ablation, cryoablation, and radiofrequency ablation. Microwave technology is a new thermal ablation technique for different types of tumors, providing all the benefits of radiofrequency and substantial advantages. Microwave ablation has been applied to liver, lung, kidney and more rarely to bone, pancreas and adrenal glands. Prelimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
175
0
15

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(194 citation statements)
references
References 30 publications
4
175
0
15
Order By: Relevance
“…In the follow-up of another studies of our Centre, patients who deceased had the progression of neoplastic disease as the cause of death, and not their poor clinical conditions, confirming this study decision to refer these patients to thermo ablative treatment [18]. Of the 24 studies analyzed, 20 [13,21,[27][28][29]31,33-37,42,43,46,48,50-54] reported patients with lung metastases, and most of them, as in our study, had origin from the colon: 17 of our patients had lung metastases (11 lesions originated from colon cancer).…”
Section: Clinical Criteriasupporting
confidence: 67%
See 3 more Smart Citations
“…In the follow-up of another studies of our Centre, patients who deceased had the progression of neoplastic disease as the cause of death, and not their poor clinical conditions, confirming this study decision to refer these patients to thermo ablative treatment [18]. Of the 24 studies analyzed, 20 [13,21,[27][28][29]31,33-37,42,43,46,48,50-54] reported patients with lung metastases, and most of them, as in our study, had origin from the colon: 17 of our patients had lung metastases (11 lesions originated from colon cancer).…”
Section: Clinical Criteriasupporting
confidence: 67%
“…From that moment on, it has been possible to perform thermal ablations in lesions with <1cm from vessels >3mm (9 cases), proximity of >1cm to heart and subclavians (1 case), and ablation of lesions with >30 mm of diameter (8 cases) (Tables 1A,1B and 2). The results regarding the Literature Review are specified on Since this study involves only thermal ablations indications, data about efficacy, safety, follow-up and complications is fully tackled in another studies of the group both, for RFA [18,22,23] and also for MWA [24].The recent MWA study has very promising results, in which MWA appears to be even better than RFA [24].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MWA would therefore be an ideal technique in case of lesion that is more than 4 cm in diameter, in contact with vessels larger than 3 mm in diameter, in patients with limited respiratory function, or in case of recurrence after thermal ablation performed by another type of energy (18).…”
Section: A B Cmentioning
confidence: 99%